(untitled) (Politeja, 2015)
‘The Union’s not so black as it’s painted’? The state of the European integration and the future of the European Union in the eyes of Poles. The qualitative analysis Debate on Polish membership in the European Union has started almost immediately after 1989. Closer to the membership negotiations and enlargement – it became more concrete even though concentrated predominantly on the conditions of membership. Even after the membership the debate on the European integration concentrated on the benefits and costs of membership. Secondly, the impact of the integration on functioning of Polish – still young and fragile – democracy in Poland was debated. Thirdly, the axiological dimension of the debate focuses on how the European integration will impact the value system in Poland. There was only little interest of the future of integration, and the debate rather focused on what would be the benefits for the country. The main aim of this article is to present how today – ten years after the enlargement – issues connected with the European integration are debated by the ordinary citizens. The special focus will be put on how they perceive the future of the European integration in the context of economic crisis in Europe.